Faktor-Faktor yang Memengaruhi Pemilihan Karir sebagai Konsultan Pajak - Arini, I Gusti Ayu Agustia; Noviari, Naniek (E-Jurnal Akuntansi, 2021)
This study aims to determine whether professional training, professional recognition, work environment, gender roles, and the influence of parents influence career choices as tax consultants. The theory used in this research is Theory of Planned Behavior (TPB). The population in this study were employees of the LMATS Consulting tax consultant and the total sample was 60 employees using the questionnaire method data collection technique with purposive sampling, namely employees of the accounting division or tax division, who have worked at least 1 year with the latest education of D3. Research location at the LMATS Consulting Tax Consultant office. The results of this study indicate that professional training, professional recognition, work environment, gender roles, and the influence of parents have a positive effect on career choices as a tax consultant in the LMATS Consulting tax consultant office. Keywords: Career; Tax Consultant; Employee.